A Hot-Cold Cognitive Model of Depression: Integrating the Neuropsychological Approach Into the Cognitive Theory Framework - Elayne Ahern; Claudi L. H. Bockting; Maria Semkovska (Clinical Psychology in Europe, 2019)
[Background] In the 50 years following Beck’s cognitive theory, empirical research has consistently supported the role of dysfunctional, ‘hot’ cognition in the onset and maintenance of major depressive disorder. Compromised ‘cold’ cognition in attention, memory, and executive control abilities, independent of the affective state, has attracted much clinical interest for its role throughout the course of illness and into remission. We propose integrating cold cognition into Beck’s cognitive theory framework to account for the complementary roles of both hot and cold cognition in depression onset and maintenance. [Method] A critical review of cognitive research was conducted to inform an integrated hot-cold cognitive model of depression. [Results] Cold cognitive deficits likely act as a gateway to facilitate the activation and expression of the hot cognitive biases through a weakened ability to attend, retrieve, and critically assess information. Cold deficits become exacerbated by the negative mood state, essentially ‘becoming hot’, lending to maladaptive emotion regulation through ruminative processes. Depleted cognitive resources contribute to the manifestation of further deficit in problem-solving ability in everyday life, which in itself, may act as a stressor for the onset of recurrent episodes, perpetuating the depressive cycle. [Conclusion] We discuss the interaction between hot and cold cognition within the cognitive theory framework and the potential of complementary hot-cold pathways to elucidate novel means of prevention and treatment for depression.